2013
DOI: 10.1021/ct400485s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dot Size on Exciton Binding Energy and Electron–Hole Recombination Probability in CdSe Quantum Dots

Abstract: Large exciton binding energy Small exciton binding energy Cd 74608 Se 74837 Cd 199 Se 195 Cd 1012 Se 1063 ΔE ΔE ΔE valence valence conduction conduction conduction valence 0 0.5 1 EBE 0 0.5 1 EBE 0 0.5 1 EBE Peh Peh Peh Radius of quantum dotExciton binding energy and electron-hole recombination probability are presented as the two important metrics for investigating effect of dot size on electronhole interaction in CdSe quantum dots. Direct computation of electron-hole recombination probability is challenging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 117 publications
13
81
1
Order By: Relevance
“…Moreover, computational studies have shown that the electron-hole recombination probability increases with an increase in !/! and decrease in NC size 93 that effectively hinders the interfacial charge transfer as well. In this context, perhaps, it is also not surprising that the 1.6 nm diameter CuInSe 2 NCs displayed the highest photocatalytic activity.…”
Section: Size Dependent Electrochemical Properties Of Fully Diffused mentioning
confidence: 99%
“…Moreover, computational studies have shown that the electron-hole recombination probability increases with an increase in !/! and decrease in NC size 93 that effectively hinders the interfacial charge transfer as well. In this context, perhaps, it is also not surprising that the 1.6 nm diameter CuInSe 2 NCs displayed the highest photocatalytic activity.…”
Section: Size Dependent Electrochemical Properties Of Fully Diffused mentioning
confidence: 99%
“…A parabolic potential was chosen because they have been used extensively 23,25,26,[100][101][102][103][104][105][106][107][108][109] to represent the confinement potential experienced by excitons in nanoparticles. The values of the force constant parameter, k, were selected such that the confining potential spanned from weakly confining region (k = 1.0 × 10 −4 a.u.)…”
Section: Physical System and Computational Detailsmentioning
confidence: 99%
“…The PL intensity Ik from the k ‐th state versus applied electric field is proportional to the electron–hole pair recombination probability. The recombination probability can be estimated as a probability that an electron and a hole are located at the same point anywhere inside the considered volume, so: IkVnormald3boldr|Ψktrue(Ltrue)true(r,rtrue)true| 2 …”
Section: The Modelmentioning
confidence: 99%